Strategi Pengembangan Jiwa Kepemimpinan Anak di Panti Asuhan Muslimat NU Darul Muhsinin Ponorogo - Dhinda Wahyu Putri Elisya; Oksiana Jatiningsih (Universitas Negeri Surabaya (Unesa), 2023)
The purpose of this study is to describe the strategies used by caregivers to develop children's leadership spirit and to describe the impacts, constraints, and solutions that occur in developing children's leadership qualities in orphanages. The focus of this research is the caregiver's strategy in developing the spirit of leadership through habituation. This study uses a qualitative approach with a descriptive method. The informants in the study were four people, namely the caregivers of the orphanage with the criteria of caregivers who were used as informants, namely caregivers in the care section, foster siblings and talents and interests. Data collection techniques used observation and unstructured in-depth interviews. While the data validity technique uses data triangulation techniques. Data analysis techniques include data reduction, data presentation and drawing conclusions. The results of this study indicate that the caregivers of the NU Darul Muhsinin Ponorogo Orphanage have provided habits as a stimulus for children in developing leadership spirit. Habituation is expected to shape the character of children who have a leadership spirit, are responsible, disciplined, independent, work hard and be creative. Equipping with religious knowledge as an effort to form the foundation of leadership character based on religious values ​​and imitating Islamic leaders. Provide habituation of responsibility and discipline to children by obeying the rules and obligations of children, and not violating the agreed rules. While the habit of discussing trains children to be able to respect the opinions of others and train to communicate. Forming a winning mentality with children participating in competition activities. Interest talent training to form children's independence and creativity. Building children's self-confidence through Child Orphanage Organizations or OPA and extracurricular activities at school. Keywords: strategy, development, leadership